2021
DOI: 10.1103/physrevfluids.6.064301
|View full text |Cite
|
Sign up to set email alerts
|

Suspension dynamics in transitional pipe flow

Abstract: Particle-laden pipe flows exhibit a gradual laminar-turbulent transition, beyond a critical volume fraction (φ). While classical transition behavior is characterized by the presence of turbulent puffs, this intermittent nature is absent for particle-induced transition. For small pipe-to-particle diameter ratios (D/d) even dilute systems exhibit this particleinduced transition behavior. In this study we use neutrally buoyant particles with a D/d of 5.7, which represents a "sweet spot," allowing the use of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Here μ 0 is the viscosity of the continuous phase (i.e., saline water or glycerol). In a previous study, the integral length scales corresponding to a smooth transition case were found to be smaller (i.e., approximately 4D in the transition region) and continuously present [14]. This is in contrast to a sharp, intermittent transition, where turbulent patches span about 20D-30D [15,18].…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…Here μ 0 is the viscosity of the continuous phase (i.e., saline water or glycerol). In a previous study, the integral length scales corresponding to a smooth transition case were found to be smaller (i.e., approximately 4D in the transition region) and continuously present [14]. This is in contrast to a sharp, intermittent transition, where turbulent patches span about 20D-30D [15,18].…”
mentioning
confidence: 80%
“…Previously, it was shown that the velocity fluctuations caused by the finite-sized particles scale with d/D. Based on this, it is expected that Re s,c is dependent on d/D and φ [14]. The latter has been shown to be a relevant scaling parameter before [8][9][10] In both plots a selection of three representative cases is shown.…”
mentioning
confidence: 90%
See 3 more Smart Citations